New approach on the development of plasticized polylactide (PLA): Grafting of poly(ethylene glycol) (PEG) via reactive extrusion - Hassouna, Fatima; Raquez, Jean-Marie; Addiego, Frédéric; Dubois, Philippe; Toniazzo, Valérie; Ruch, David (European polymer journal, 2011)
[Display omitted] ► Development of new way of plasticizing PLA with PEG via reactive extrusion. ► In situ reactive blending performance of anhydride-grafted PLA copolymer with PEG. ► Improvement of PLA thermal and mechanical properties in the reactive blend. In this work, new ways of plasticizing polylactide (PLA) with low molecular poly(ethylene glycol) (PEG) were developed to improve the ductility of PLA while maintaining the plasticizer content at maximum 20wt.% PLA. To this end, a reactive blending of anhydride-grafted PLA (MAG-PLA) copolymer with PEG, with chains terminated with hydroxyl groups, was performed. During the melt-processing, a fraction of PEG was grafted into the anhydride-functionalized PLA chains. The role of the grafted fraction was to improve the compatibility between PLA and PEG. Reactive extrusion and melt-blending of neat and modified PLA with PEG did not induce any dramatic drop of PLA molecular weight. The in situ reactive grafting of PEG into the modified PLA in PLA/PEG blends showed a clear effect on the thermal properties of PLA. It was demonstrated by DSC that the mobility gained by PLA chains in the plasticized blends yielded crystallization. The grafting of a fraction of PEG into PLA did not affect this process. However, DSC results obtained after the second heating showed an interesting effect on the Tg when 20wt.% PEG were melt blended with neat PLA or 10wt.% MAG-PLA. In the latter case, the Tg displayed by the reactive blend was shifted to even lower temperatures at around 14°C, while the Tg of neat PLA and PLA blended with 20wt.% PEG was around 60 and 23°C, respectively. Regarding viscoelastic and viscoplastic properties, the presence of MAG-PLA does not significantly influence the behavior of plasticized PLA. Indeed, with or without MAG-PLA, elastic modulus and yield stress decrease, while ultimate strain increases with the addition of PEG into PLA.